Total Pancreatectomy for Malignant Intraductal Papillary Mucinous Neoplasm (IPMN) Complicated by Gastropancreatic Fistulae - Oshan Basnayake; Pradeep Wijerathne; Umesh Jayarajah; Nilesh Fernandopulle; Sivasuriya Sivaganesh (Case Reports in Surgery)
Background. Intraductal papillary mucinous neoplasms (IPMN) of the pancreas complicated by fistula formation to adjacent organs are an uncommon phenomenon. We present an IPMN of the pancreas with malignant transformation and multiple fistulae to the stomach and duodenum. Case Presentation. A 50-year-old female was referred for investigation of recent epigastric pain and a past history of recurrent pancreatitis. Imaging with computed tomography showed a gross dilatation of the entire pancreatic duct with a heterogeneous enhancement of the periductal parenchyma. A passage of oral contrast was noted from the greater curvature and pylorus of the stomach into the dilated duct suggestive of fistulae formation. Gastroduodenoscopy demonstrated these fistulae in the stomach and the proximal duodenum and an exophytic growth at the ampulla obliterating the view of ampullary opening. Endosonography- (EUS-) guided fine-needle aspiration cytology (FNAC) showed cells with high-grade atypia. A total pancreatectomy, distal gastrectomy, and splenectomy were performed, and recovery was uneventful. Histology revealed a ductal adenocarcinoma arising from an intestinal type intraductal papillary mucinous neoplasm with high-grade dysplasia. A year and a half after surgery, she is healthy with good glycaemic control and nutritional status. Conclusion. This case highlights the importance investigating patients for the aetiology in recurrent acute pancreatitis and their follow-up. Awareness of cystic pancreatic neoplasms including IPMN is important to avoid misdiagnosis or delayed diagnosis. Referral of these patients to centres with facilities for multidisciplinary input and specialised management is strongly recommended.